Anti-allergic Hydroxy Fatty Acids from Typhonium blumei Explored through ChemGPS-NP - Korinek, Michal; Tsai, Yi-Hong; El-Shazly, Mohamed; Lai, Kuei-Hung; Backlund, Anders; Wu, Shou-Fang; Lai, Wan-Chun; Wu, Tung-Ying; Chen, Shu-Li; Wu, Yang-Chang; Cheng, Yuan-Bin; Hwang, Tsong-Long; et al. (Frontiers in Pharmacology, 2017)
Increasing prevalence of allergic diseases with an inadequate variety of treatment drives forward search for new alternative drugs. Fatty acids, abundant in nature, are regarded as important bioactive compounds and powerful nutrients playing an important role in lipid homeostasis and inflammation. Phytochemical study on Typhonium blumei Nicolson & Sivadasan (Araceae), a folk anti-cancer and anti-inflammatory medicine, yielded four oxygenated fatty acids, 12R-hydroxyoctadec-9Z,13E-dienoic acid methyl ester (1) and 10R-hydroxyoctadec-8E,12Z-dienoic acid methyl ester (2), 9R-hydroxy-10E-octadecenoic acid methyl ester (3), and 12R*-hydroxy-10E-octadecenoic acid methyl ester (4). Isolated compounds were identified by spectroscopic methods along with GC-MS analysis. Isolated fatty acids together with a series of saturated, unsaturated and oxygenated fatty acids were evaluated for their anti-inflammatory and anti-allergic activities in vitro. Unsaturated (including docosahexaenoic and eicosapentaenoic acids) as well as hydroxylated unsaturated fatty acids exerted strong anti-inflammatory activity in superoxide anion generation (IC50 2.14 – 3.73 µM) and elastase release (IC50 1.26 – 4.57 µM) assays. On the other hand, in the anti-allergic assays, the unsaturated fatty acids were inactive, while hydroxylated fatty acids showed promising inhibitory activity in A23187- and antigen-induced degranulation assays (e.g. 9S-hydroxy-10E,12Z-octadecadienoic acid, IC50 92.4 and 49.7 µM, respectively). According to our results, the presence of a hydroxy group in the long chain did not influence the potent anti-inflammatory activity of free unsaturated acids. Nevertheless, hydroxylation of fatty acids (or their methyl esters) seems to be a key factor for the anti-allergic activity observed in the current study. Moreover, ChemGPS-NP was explored to predict the structure-activity relationship of fatty acids. The anti-allergic fatty acids formed different cluster distant from clinically used drugs. The bioactivity of T. blumei, which is historically utilized in folk medicine, might be related to the content of fatty acids and their metabolites.